Monitoring Drought Events and Vegetation Conditions in Pakistan: Implications for Drought Management and Food Security - Rabia Tabassum; Imran Ahmed Khan; Mudassar Hassan Arsalan (Proceedings of the Pakistan Academy of Sciences: A. Physical and Computational Sciences, 2023)
Drought is an environmental and humanitarian concern, affecting various regions and landscapes with detrimental impacts on the natural environment and human lives. It is crucial to have access to accurate and timely information on vegetation conditions to mitigate its effects, which is possible through remote sensing techniques. The Google Earth Engine (GEE) platform offers powerful tools and a vast collection of geospatial data that can improve drought monitoring efforts. In Pakistan, a country prone to droughts and natural disasters, this study employs GEE to monitor drought events over croplands and determine their severity using indices such as Vegetation Health Index (VHI), Vegetation Condition Index (VCI), and Temperature Condition Index (TCI). Additionally, the study generates mean yearly and monthly VHI maps, allowing for the observation of trends in drought occurrences over time. Analysis of yearly and monthly mean VHI maps reveals that in 2001 and 2002, the Pakistan cropland experienced severe to moderate drought. From 2011 to 2021, overall drought occurrences were relatively low, and the annual VHI reflected healthy vegetation conditions. The study emphasizes the adequacy of vegetation in 2019, 2020, and 2021. Notably, agricultural areas in Punjab demonstrate sufficient soil moisture and healthy vegetation, while in Sindh, cropland is predominantly affected by severe to moderate drought, characterized by a continuous deficiency of soil moisture. Temporal variations highlight an increasing trend in VHI, indicating a promising outlook for healthy vegetation in Pakistan's cropland. This study provides valuable information for drought management, planning, water resource management, food production, and food security.